Progress of CT aortic angiography combined with coronary artery in the evaluation of acute aortic syndrome - An, Hengbin; Xie, Ruigang; Ge, Yinghui; Wang, Tianyun (Frontiers in Cardiovascular Medicine, 2022)
Acute aortic syndrome (AAS) is a group of cardiovascular diseases that seriously threaten human life and health. AAS patients are often complicated with coronary artery disease and other related diseases, which requires rapid and clear clinical diagnosis to avoid serious adverse events. In recent years, with the progress of science and technology, a variety of CT angiography techniques have been applied in clinic, and the diagnosis rate of AAS with Coronary heart disease (CAD) has been greatly increased. At the same time, the development of surgical technology and endovascular repair technology has significantly reduced the mortality and complication rate of AAS surgery. In clinical diagnosis of AAS and related diseases, CT aortic angiography (CTA) combined with coronary CTA is increasingly applied to identify related diseases. Here, the current research progress on the technique of aortic CTA combined with coronary CTA was reviewed.